Accreditation Engineering Scenario and Future of Engineering Education in Malaysia - Tan, CheeFai; Ranjit, S.S.S.; Ong, S.T.; Ngeow, Y.W. (2011)
Engineering education in Malaysia is a strong and vibrant enterprise. Malaysia government is projecting to produce 222,000 engineering graduates in the next 9 years. This number of engineers is needed to ensure the development industries, infrastructures and general well-being of Malaysia are carried out as planned. However, since Malaysia has engineers in various fields, engineers have provided the driving forces behind high technology services and products to enhance the Malaysia economy growth locally and internationally. It is also cited that there are 33 accredited engineering programmes in Malaysia universities and colleges. Engineering degree is the common degree entry to the engineering profession nowadays, such as civil engineering, electrical engineering, electronics engineering and mechanical engineering. The Malaysia engineering degree requires a completion of four years full time study. For an engineering degree programme to be recognize, all the engineering degrees in Malaysia are governed by Engineering Accreditation Council (EAC). EAC ensure all the engineering degree programmes that are offered by Malaysian universities are subjected to the minimum academic requirements for registration as a graduate engineer with the Board of Engineers Malaysia (BEM). BEM is representing Malaysia in Washington Accord since 2009, engineering education in Malaysia took on a broader international aspect and agreed to achieve equivalent standard with the other 14 signatories’ countries. Due to the upcoming challenges of the future, it is ideated that Malaysia engineers must progress working hard with all the necessary technical competencies in engineering science. This role is very important so that they will be flexible enough to be involved in multidisciplinary engineering tasks in Malaysia and around the world.